Darar or harm for failure to maıntaın the wıfe: A quranıc and Jurıstıca approach on marrıage dıssolutıon - Tengku Muda, Tengku Fatimah Muliana; Mohd, Azizah; Md Hashim, Noraini (International Journal of Academic Research in Business and Social Sciences, 2017)
The Islamic principle on prevention of harm or darar is well established in the Qur’an, narrated in the narrations of the Prophets and had long been discussed by classical jurists. The commentaries of the Quran explained the term ‘darar’ in various dimensions and meanings as according to the verses to include al-huznu or grief, fear and horror, distress and illness, as well as poverty and hardship. In view of this, Islamic law imposes a financial duty on the husband to maintain his wife and that his failure will bring harm to the wife. The duty arises as soon as the marriage completed and ends either through death or separation. This paper seeks to examine the juristic views of different schools of laws in Islam (mazahib) on the husband’s duty to financially support and maintain the wife, as well as the effect of non-maintenance. Content analysis method is employed where references is made to commentaries of the Quran as well as classical jurists’ texts, contemporary references of Islamic jurisprudence, narrations of the Prophet PBUH and relevant sources. Few selected Syariah court cases will also be discussed to support the premise. The findings indicate that where the husbands failed to provide for the wife’s maintenance for a certain period of time, it causes not only financial difficulties to the wife but extends far more to an abuse which justifies a judicial dissolution of marriage. Keywords: : Emotional abuse, Fasakh, Harm, Wife’s maintenance